A decision support system for long-term capacity management of call centres. (15th November 2021) - Yaczola, Stephen A.; Slotnick, Susan A.
We develop a decision support system (DSS) for the computationally complex problem of long-term personnel planning in call centres which employs a novel approach to analyse the consequences of decisions about the number of call-centre agents and their allocation to different tasks, in the light of multiple performance objectives (labour budget, service level, and non-primary productive time). Using actual call-centre data, our validation study shows that the DSS performs well when compared to the historical managerial decisions, and is robust to increased demand variability. This research fills a gap in the literature on call-centre staffing, which has focused on short-term personnel scheduling. The DSS is an interactive decision-making tool that provides quantitative insights to call-centre managers, recommending actions to minimise deviation from plan among multiple performance objectives, as well as enabling managers to evaluate the potential effect of their decisions on those objectives in the current and successive years.